Tecnologia social: o papel do Terceiro Setor no fomento de inovações para a sociedade - Fernandes, Carlos Roberto Oliveira Cesar (2014)
This work presents an investigation on the development of social technologies by the organizations of the Third Sector. The purpose is to analyze how the elements of participation, dialogue, innovation, knowledge and management are conducted by institutions that are not part of the State and market. Based on the concepts of citizenship and democracy, this work relates the social technologies to a dialogical and critical behavior according to the reality. The result, finally, repositions the Third Sector through a critical paradigm, emphasizing that the learning through social technologies, can be an instrument of transformation in different contexts, since the theory until the practice.